Using Alcohol Unit-marked Glasses Enhances Capacity To Monitor Intake: Evidence From a Mixed-method Intervention Trial. (10th November 2016) - de Visser, Richard; Brown, Clare; Cooke, Richard; Cooper, Greg; Memon, Anjum
Abstract: Aims: In the UK, people tend to have poor knowledge of government guidelines for alcohol use, and lack the motivation and skills required to use them to monitor their drinking. The study aim was to determine whether using glasses marked with such guidelines would improve knowledge and attitudes, increase frequency of counting units and lower alcohol intake. Methods: A total of 450 adults in the UK participated in an intervention vs control study with 1-month follow-up. The intervention group was encouraged to use glasses supplied by the researchers that indicated the unit content of drinks of different strengths and volumes, and stated the intake guidelines. Data were collected online. A further more in-depth interview with 13 intervention group participants enquired into their experiences of using the glasses. Results: Analyses adjusted for baseline variables showed that the intervention improved the following: knowledge of unit-based guidelines, ability to estimate the unit content of drinks, attitudes toward the guidelines and frequency of counting unit intake. However, there was no significant difference in alcohol consumption between the groups at follow-up. Interviews suggested that the glasses encouraged people to think about their drinking and to discuss alcohol with other people. The design of the glasses was not appealing to all, and their initial impact did not always persist. Conclusion: Use of unit-marked glasses led to changes in people's reported use of unit-based guidelines to monitor their drinking but, in the short term, no change in consumption. Qualitative data suggested that the glasses could have an impact at the individual level (on knowledge and attitudes) and at a broader level (by prompting discussion of alcohol use).